2021
DOI: 10.3390/medicina58010046
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Analgesics with Cisplatin: Modulation of Anticancer Efficacy and Potential Organ Toxicity

Abstract: Cisplatin (CDDP), one of the most eminent cancer chemotherapeutic agents, has been successfully used to treat more than half of all known cancers worldwide. Despite its effectiveness, CDDP might cause severe toxic adverse effects on multiple body organs during cancer chemotherapy, including the kidneys, heart, liver, gastrointestinal tract, and auditory system, as well as peripheral nerves causing severely painful neuropathy. The latter, among other pains patients feel during chemotherapy, is an indication for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 109 publications
1
5
0
Order By: Relevance
“…Hence the ANOVA results suggest that the percentage of inhibition of alpha interferon was significant. These findings are consistent with previous findings that indicate that alpha-interferon suppresses tumor growth in colon cancer [ 12 16 ]. The in vivo anticancer activity of alpha interferon is proven in other cancers.…”
Section: Discussionsupporting
confidence: 94%
“…Hence the ANOVA results suggest that the percentage of inhibition of alpha interferon was significant. These findings are consistent with previous findings that indicate that alpha-interferon suppresses tumor growth in colon cancer [ 12 16 ]. The in vivo anticancer activity of alpha interferon is proven in other cancers.…”
Section: Discussionsupporting
confidence: 94%
“…DCF is also known as a non-selective Cox inhibitor and plays a role in the inhibition of prostaglandin synthesis, the inhibition of lipoxygenase enzymes and the activation of the nitric oxide–cGMP antinociceptive pathway [ 13 ]. Previous studies have reported that the use of NSAID in combination with chemotherapeutic drugs effectively potentiated anticancer efficacy [ 14 , 15 ]. Among these outcomes, DCF has been proven to be able to enhance the cytotoxicity of cisplatin in cancer cells [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Octahedral platinum is considered inert but the modification of the axial position can effectively be utilized for further design and development. Several studies were conducted by combining the platinum drugs with non-steroidal anti-inflammatory agents such as aspirin, ibuprofen, flurbiprofen, naproxen etc as axial ligands (77,78). The General structures of the platinum-NSAID prodrugs were given in figure 7.…”
Section: Platinum-nsaids Prodrugsmentioning
confidence: 99%